PENGARUH PENAMBAHAN KUNYIT DAN METODE PENGEMASAN TERHADAP DAYA AWET FILET LELE ASAP SELAMA PENYIMPANAN SUHU KAMAR - , S FAJAR HANGGA KUMARA, Nurfitri Ekantari, S.Pi., M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this study was to determine the effect of turmeric addition and packaging methods on shelf life of smoked catfish fillets during ambient storage. This study used a completely randomized design, consisted of nine treatments, there were control (added liquid smoke and turmeric without packaging)